Transparency in Government of Canada Public Procurement Practices: Beyond Vision and Voice? - Arhoma, Othman Zidan (Université d'Ottawa / University of Ottawa, 2025)
This dissertation investigates how transparency is operationalized by the Government of Canada (GoC) in the procurement activities it conducts through the Buyandsell.gc.ca and Proactive Disclosures - Contract Dataset platforms. The former is the central hub for federal-level procurement activities, and the latter is the key hub for accessing information about government contracts and expenditures. Drawing upon Meijer, Curtin, and Hillebrandt's (2012) vision and voice framework for investigating transparency, this dissertation asks: How are vision and voice manifest in GoC procurement activities that occur via its two main procurement platforms? A multi-method qualitative approach, combining desk-based analysis of the Buyandsell.gc.ca and Proactive Disclosures - Contract Dataset platforms and 13 semi-structured interviews with private sector, civil society, and federal government key informants was used to investigate this question. The desk-based phase focused on visibility, assessing information accessibility, usability, and quality at the platforms. The second phase focused on constraints hindering information visibility for stakeholders and its implications for their interests being heard. Private sector participants reported difficulties in accessing timely and relevant information needed to engage in transactions and transparency-related policy discussions. Civil society participants emphasized systemic barriers to meaningful engagement as impediments to achieving transparency. Government officials stressed operational challenges as the key impediments to meeting transparency objectives. Given the small size of the research sample, the findings of this study are necessarily tentative but do suggest a need both for expanding the conceptualization of voice within the Meijer et al. (2012) framework and for revisiting how procurement-related transparency initiatives are designed and implemented.
Keywords: Transparency; Digital public procurement; Government of Canada; Visibility of information; Stakeholder engagement; Vision-voice framework; E-procurement platforms; Open government